2023
DOI: 10.1002/alz.12980
|View full text |Cite
|
Sign up to set email alerts
|

Genetic propensity for cerebral amyloidosis and risk of mild cognitive impairment and Alzheimer's disease within a cognitive reserve framework

Abstract: INTRODUCTIONWe constructed a polygenic risk score (PRS) for β‐amyloid (PRSAβ42) to proxy AD pathology and investigated its association with incident Alzheimer's disease (AD)/amnestic mild cognitive impairment (aMCI) and the influence of cognitive reserve (CR), proxied by educational years, on the relationship between PRSAβ42 and AD/aMCI risk.METHODSA total of 618 cognitive‐normal participants were followed‐up for 2.92 years. The association of PRSAβ42 and CR with AD/aMCI incidence was examined with COX models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…Additionally, an additive interaction was observed between PRSAβ42 and CR, whereby individuals with high levels of CR and PRSAβ42 showed a 62.6% reduction in the risk of developing aMCI/AD compared to those with high levels of PRSAβ42 alone. 33 These findings provide support for the CR hypothesis, indicating that early-life education may lessen the impact of genetically mediated amyloid accumulation on the development of aMCI/AD.…”
Section: Genetic Factors and Crsupporting
confidence: 61%
See 3 more Smart Citations
“…Additionally, an additive interaction was observed between PRSAβ42 and CR, whereby individuals with high levels of CR and PRSAβ42 showed a 62.6% reduction in the risk of developing aMCI/AD compared to those with high levels of PRSAβ42 alone. 33 These findings provide support for the CR hypothesis, indicating that early-life education may lessen the impact of genetically mediated amyloid accumulation on the development of aMCI/AD.…”
Section: Genetic Factors and Crsupporting
confidence: 61%
“…Additionally, an additive interaction was observed between PRSAβ42 and CR, whereby individuals with high levels of CR and PRSAβ42 showed a 62.6% reduction in the risk of developing aMCI/AD compared to those with high levels of PRSAβ42 alone. 33 These findings provide support for the CR hypothesis, indicating that early‐life education may lessen the impact of genetically mediated amyloid accumulation on the development of aMCI/AD. These results have significant clinical implications, as they suggest that interventions designed to enhance CR, whether implemented early or later in life, could potentially delay cognitive decline and prevent AD, even in individuals at high genetic risk for amyloid brain pathology.…”
Section: Genetic Factors and Crsupporting
confidence: 61%
See 2 more Smart Citations
“…Calling was generated by the 'Centre National de Recherche en Génétique Humaine' (Evry, France) using the data generated by the centers involved in genotyping (Life & Brain, Bonn, Germany, CNRGH, Evry, France and Erasmus Medical Center, Rotterdam, Netherlands) [29]. Further information regarding the genotyping and imputation in the HELIAD study have been described in a previously published work [30] and can be found in the Supplementary Materials.…”
Section: Genotyping and Imputationmentioning
confidence: 99%